Pengaruh Suasana Café, Lokasi dan Inovasi Terhadap Minat Beli di Bengkel Kopi Bandar Lampung - Pranajaya, Andre Raevaldy; Warganegara, Tri Lestira Putri (Jurnal EMT KITA, 2024)
This study aims to analyze the influence of café atmosphere, location, and innovation on purchase intention at Bengkel Kopi Bandar Lampung. Bengkel Kopi is a unique restaurant that offers the concept of enjoying food and beverages, especially coffee, in a serene and comfortable environment. The restaurant provides playing facilities for customers, whether friends or family, while waiting for their orders. This research uses a quantitative method with a survey approach. The population consists of 4,559 people who participated in the Bandar Lampung coffee workshop in 2022, and a sample of 98 people was selected using the convenience sampling method. Data were collected through observation and analyzed using multiple regression analysis with SPSS version 22. The results show that café atmosphere, location, and innovation significantly influence purchase intention. Café atmosphere and location have a positive impact on purchase intention, while innovation contributes the most